Immunomodulatory effects of low dose chemotherapy and perspectives of its combination with immunotherapy - Nars, Mariana S. [UNESP]; Kaneno, Ramon [UNESP] (Wiley, 2013)
Given that cancer is one of the main causes of death worldwide, many efforts have been directed toward discovering new treatments and approaches to cure or control this group of diseases. Chemotherapy is the main treatment for cancer; however, a conventional schedule based on maximum tolerated dose (MTD) shows several side effects and frequently allows the development of drug resistance. On the other side, low dose chemotherapy involves antiangiogenic and immunomodulatory processes that help host to fight against tumor cells, with lower grade of side effects. In this review, we present evidence that metronomic chemotherapy, based on the frequent administration of low or intermediate doses of chemotherapeutics, can be better than or as efficient as MTD. Finally, we present some data indicating that noncytotoxic concentrations of antineoplastic agents are able to both up-regulate the immune system and increase the susceptibility of tumor cells to cytotoxic T lymphocytes. Taken together, data from the literature provides us with sufficient evidence that low concentrations of selected chemotherapeutic agents, rather than conventional high doses, should be evaluated in combination with immunotherapy. Copyright © 2012 UICC.
Keywords: chemotherapy; dendritic cells; immunotherapy; metronomic; Treg; vaccine; 5 aza 2' deoxycytidine; adenovirus vector; antineoplastic agent; bevacizumab; celecoxib; cetuximab; cisplatin; cyclophosphamide; dendritic cell vaccine; docetaxel; doxorubicin; etoposide; fluorouracil; folinic acid; gemcitabine; granulocyte colony stimulating factor; idarubicin; interleukin 12; irinotecan; mercaptopurine; methotrexate; mitomycin; mitoxantrone; oxaliplatin; paclitaxel; rofecoxib; tumor cell vaccine; unindexed drug; vinblastine; vincristine; advanced cancer; alopecia; antiangiogenic activity; antineoplastic activity; arthralgia; bleeding; blood toxicity; bone marrow suppression; brain damage; breast cancer; breast metastasis; cancer chemotherapy; cancer combination chemotherapy; cancer immunotherapy; cancer resistance; colon cancer; colon carcinoma; colorectal cancer; cytokine response; cytotoxic T lymphocyte; depression; digestive system function disorder; DNA methylation; dose calculation; dose response; drug cytotoxicity; drug megadose; drug potentiation; drug safety; drug sensitivity; heat injury; Hodgkin disease; human; immunological tolerance; immunomodulation; immunostimulation; infection; leukemia; leukopenia; liver toxicity; low dose metronomic chemotherapy; low drug dose; lung carcinoma; lung non small cell cancer; lymphocytopenia; lymphoma; maintenance therapy; malignant neoplastic disease; maximum tolerated dose; melanoma; mucosal disease; multiple myeloma; neoplasm; neuroblastoma; neutropenia; nonhuman; ovary cancer; priority journal; review; side effect; single drug dose; stomach tumor; T cell depletion; thrombocytopenia